Исследование кристаллов Cu₂ZnSnTe₄ и гетеропереходов на их основе - Ковалюк, Т.Т.; Солован, М.Н.; Мостовой, А.И.; Майструк, Э.В.; Пархоменко, Г.П.; Марьянчук, П.Д. (Технология и конструирование в электронной аппаратуре, 2015)
Представлены результаты исследований магнитных, кинетических и оптических свойств кристаллов Cu₂ZnSnTe₄. Методом магнетронного осаждения тонких пленок TiN, TiO₂ и МоОх на подложки из кристаллов Cu₂ZnSnTe₄ изготовлены анизотипные гетеропереходы n-TiN/p-Cu₂ZnSnTe₄, n-TiO₂/p-Cu₂ZnSnTe₄ и n-MoO/p-Cu₂ZnSnTe₄. Исследованы их электрические свойства и установлены доминирующие механизмы токопереноса при прямом и обратном смещениях. Представлено результати досліджень магнітних, кінетичних і оптичних властивостей кристалів Cu₂ZnSnTe₄. Методом магнетронного напилення тонких плівок TiN, TiO₂ та МоОх на підкладки з кристалів Cu₂ZnSnTe₄ виготовлено анізотипні гетеропереходи n-TiN/p-Cu₂ZnSnTe₄, n-TiO₂/p-Cu₂ZnSnTe₄ і n-MoO/p-Cu₂ZnSnTe₄. Досліджено їх електричні властивості і встановлено домінуючі механізми струмопереносу при прямих і зворотних зміщеннях. The paper reports on the results of the studies of magnetic, kinetic and optical properties of Cu₂ZnSnTe₄ crystals. The Cu₂ZnSnTe₄ crystals showed diamagnetic properties (the magnetic susceptibility almost independent of the magnetic field and temperature). The Cu₂ZnSnTe₄ crystals possessed p-type of conductivity and the Hall coefficient was independent on temperature. The temperature dependence of the electrical conductivity of the Cu₂ZnSnTe₄ crystal shows metallic character, i. e. decreases with the increase of temperature, that is caused by the lower charge carrier mobility at higher temperature. Thermoelectric power of the samples ispositive that also indicates on the prevalence of p-type conductivity.